Perioperative Short-Term Outcome in Super-Super-Obese Patients Undergoing Bariatric Surgery - Anna Dupree and Alexander Tarek El Gammal and Stefan Wolter and Silvana Urbanek and Nina Riedel and Oliver Mann and Philipp Busch (Obesity Surgery, 2018)
Background